Weaver syndrome in a 16-year-old child (clinical case description) - T. A. Bokova; D. A. Kartashova; Yu. Yu. Kotalevskaya (Лечащий Врач)
In their practice, pediatricians often observes patients with significant disorders in their physical development. In most cases, these changes are related to dwarfism and quite often conditioned by hereditary factors. But special attention should be paid to children with high anthropometric parameters. The article presents a case of own observation of extremely rare combination of tallness and congenital disorders in development – Weaver syndrome in a 16-year-old adolescent.